INTERCULTURAL COMMUNICATION ACCOMMODATION OF MALAYSIA STUDENTS AT SUNAN AMPEL STATE ISLAMIC UNIVERSITY SURABAYA - Sihabuddin, Sihabuddin; Rizqi, Fikriana Mahar (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
The background of this research aims to find out how intercultural communication accommodation of Malaysian student at Sunan Ampel State Islamic University Surabaya, so that there is harmonious relationship with the people around them especially in lecture activities. The purpose of this study is to analyze and describe intercultural communication accommodation of Malaysian students at Sunan Ampel State Islamic University Surabaya, especially in convergence and divergence. The research method uses qualitative methods with a case study approach. The results showed that students from Malaysia at Sunan Ampel State Islamic University Surabaya carried out intercultural communication accommodation due to their self-awareness of cultural differences, openness in interaction and a high willingness to learn new cultures and practice them in everyday life. Even so, not all forms of communication in the new culture were adapted in everyday life because they were considered not appropriate to the culture in their hometown in Malaysia. The convergence form of intercultural communication accommodation is by learning Indonesian and Javanese to the closest people, and practicing it by trying to use an accent in accordance with the people around them. The divergence form of intercultural communication accommodation is by maintaining communication distance between types or not being too close physically like students in general. In addition, female students still wear the clothes they usually wear in their hometowns, namely ‘Baju Kurung’ combined with a wide veil. Meanwhile, students often wear Malaysian Malay clothing for religious activities. Keywords: Communication Accommodation, Intercultural Communication, Malaysian Student, Convergence, Divergence.